he Level of Knowledge of Final Year Dental Students about the Ways to Diagnose OSCC Lesions - Mansoor Sardarpour; Atousa Aminzadeh Gohari (Isfahan University of Medical Sciences, 2023)
Oral cancer is a prevalent malignant tumor among head and neck cancers, and Oral squamous cell carcinoma (OSCC) accounts for 90% of oral cancers. Early diagnosis and treatment is the most important factor in reducing the mortality of OSCC, the purpose of this study is to investigate the level of awareness of final year dental students at Isfahan Azad University about the methods used to diagnose OSCC lesions.Materials & Methods:In this cross-sectional descriptive study, which was conducted in the academic year of 2021-2022 among 82 final year students from the Faculty of Dentistry at Isfahan Azad University, a research questionnaire was distributed among the students. Data analysis was done in two descriptive and inferential sections. The collected data were analyzed using non-parametric Mann-Whitney test and Spearman correlation coefficient at the error level of 0.05% (p value <0.05).Results:The findings of the current research indicate that 47.9% of female students and 52.1% of male students; 80.5% of students were single, 19.5% were married, 74.4% were native and 25.6% were non-native. The average knowledge score was above average (3.48 out of 6), and there were no significant differences in the average knowledge scores between male and female students, single and married, and native and non-native (p value > 0.05).Conclusion:The results of the present study showed that the level of knowledge and awareness among final year dental students of Isfahan Islamic Azad University in relation to the diagnosis of OSCC lesions is average and far from the ideal level.Key words:Knowledge;Carcinoma;Squamous cell;Epithelial Cells; Diagnosis